2018
DOI: 10.1590/1413-70542018423006818
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic methods applied in reference evapotranspiration modeling

Abstract: The importance of the precise estimation of evapotranspiration is directly related to sustainable water usage. Since agriculture represents 70% of Brazil’s water consumption, adequate and efficient application of water may reduce the conflicts over the use of water among the multiple users. Considering the importance of accurate estimation of evapotranspiration, the objective of the present study was to model and compare the reference evapotranspiration from different heuristic methodologies. The standard Penm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
8
0
4
Order By: Relevance
“…Hence, these findings correspond to the higher data dispersion and are represented by the coefficient of determination (Figure 3), 0.66 and 0.58, respectively. These results are according to Althoff et al (2018) that modeling and comparing the ETo from different heuristic methodologies confirmed that Thornthwaite's method resulted in a lower determination coefficient, R 2 = 0.39. Some findings by Sales et al (2018) and Oliveira et al (2020) also obtained similar responses to this study with "good" performance in the ETo estimates, on a daily scale, using the empirical method JH.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Hence, these findings correspond to the higher data dispersion and are represented by the coefficient of determination (Figure 3), 0.66 and 0.58, respectively. These results are according to Althoff et al (2018) that modeling and comparing the ETo from different heuristic methodologies confirmed that Thornthwaite's method resulted in a lower determination coefficient, R 2 = 0.39. Some findings by Sales et al (2018) and Oliveira et al (2020) also obtained similar responses to this study with "good" performance in the ETo estimates, on a daily scale, using the empirical method JH.…”
Section: Resultssupporting
confidence: 63%
“…Since agriculture represents 70% of Brazil's water consumption, the correct ETo estimation supports the farmer's decision about the quantity the irrigation depth should be supplied to the soil during crop cycle and irrigation frequency (Oliveira et al, 2020). Consequently, the plant does not suffer from a deficit or excess of water, which in turn causes a reduction in productivity and environmental impacts, such as leaching of nutrients and soil salinization (Althoff et al, 2018).…”
Section: Issn:1984-2295mentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, there is also the fact that NRPB aggregates predictive information into the models tested, explaining facts that cannot be elucidated only with the backscatter information. The insertion of the NRPB variable in machine learning models, like rf, helps the results to reach better statistical metrics in the validations, and consequently leads to greater generalization capacity in the models [48,49], since these kinds of models are recognized for having a high capacity for pattern recognition and complex solutions [6].…”
Section: Discussionmentioning
confidence: 99%
“…From a diverse number of models developed in the literature for estimating ETo, the Penman-Monteith (PM) standardized by FAO 56 (Allen et al, 1998) has been widely used as a reference for calibrating a diverse number of methods (Althoff et al, 2018;Feng et al, 2017;Ferreira et al, 2019;Shiri et al, 2014). Penman-Monteith's ETo is calculated as follows: the mean saturation vapor pressure for a day, kPa; e a = actual vapor pressure, kPa; Δ = slope of saturation vapor pressure curve at air temperature (kPa °C-1 ); and, γ = psychrometric constant (kPa °C-1 ).…”
Section: Fao Penman-monteithmentioning
confidence: 99%